Introducing a system operator in the waste management industry by adapting lessons from the energy sector - Di Foggia, Giacomo; Beccarello, Massimo (Frontiers in Sustainability, 2022)
Governance of waste management is historically based on local issues, with different applications and rules across countries. To meet the increasing number of circular economic goals, countries worldwide are seeking to improve the efficiency of waste management markets in terms of environmental performance and cost efficiency. For this market to effectively move towards a more circular perspective, sound reforms are needed at the market design level. We suggest that a system operator should be introduced in the industry to coordinate and support the healthy functioning of the market. We develop our idea starting from lessons learned from the energy market that apply governance characteristics and environmental goals. Focusing on the industry structure, we identify tasks and duties that a waste management system operator should perform to boost the transition towards a more circular economy. Our proposal has policy ramifications, with the most important identifying an appropriate legal entity. The study has managerial implications, and we suggest that a system operator is needed for reporting environmental results, ensuring the universality of service, planning and monitoring environmental goals, and supporting local authorities, as well as other coordination activities. These activities will facilitate a move towards a more circular economy, addressing issues concerning the complexity of waste management industries, markets, and outputs.